HOW ESL LEARNERS WITH DIFFERENT PROFICIENCY LEVELS HANDLE UNFAMILIAR VOCABULARY IN READING - Wang Dakun (Indonesian JELT, 2007)
This article presents findings from research into spontaneous vocabulary handling strategies employed by a sample of 20 Singapore secondary students from a typical neighborhood school. Following the definition of the term ‘strategy’ referring to a specific action or step, I identified 21 types of strategies used by the participants, and compared the way the high and low proficiency students employed them by comparatively examining the majority usage strategies of the two groups. To find the evidence of their strategy use, think-aloud protocols paired with immediate retrospective interviews and general interviews when necessary were analyzed. The study showed that the students mobilized multiple strategies on individual words and that the high proficiency students used strategies both more flexibly and effectively than their low proficiency counterparts. The differences in the use of strategies between the groups suggest a need for learner strategy training and awareness raising, an issue which is also discussed in this article. Keywords:   vocabulary handling strategies, think-aloud protocols interviews